Outside the pattern: Evolution of the genital asymmetry in Saicinae (Hemiptera: Heteroptera: Reduviidae) - Castro Huertas, Valentina (2023)
Despite genital structures in insects being consistently important as systematic and taxonomy evidence, within assassin bugs (Heteroptera, Reduviidae) at least, the male and female genitalic structures of several subfamilies are poorly or totally unknown. The genital structure is mostly symmetric within Saicinae genera, but male genital asymmetry has been recorded in Gallobelgicus, Polytoxus, and recently Pseudosaica. The subfamily has been considered as closely related to Emesinae and Visayanocorinae but this hypothesis has never been tested using a comprehensive taxa sampling, being a constraint to test morphological traits changes or exploring characters' evolution hypotheses. Here, we compiled a morphological data set of 170 characters that includes external morphological characters and genitalia of both sexes of Saicinae which was analyzed cladistically including 55 terminals, comprising 16 genera (64% of the generic diversity), 43 species of Saicinae and 12 outgroups. Saicinae was recovered as polyphyletic, Saicireta correntina is recovered as sister-species of Empicoris armatus + Collartida (Emesinae), Oncerotrachelus, Carayonia (Visayanocorinae), and the Clade Saicinae sensu stricto. Carayonia orientalis is recovered as sister-species of Saicinae sensu stricto. Ancestral state reconstruction of symmetry of the male genitalia shows an ancestor with symmetric male genitalia, two independent emergences of asymmetrical male genitalia within Saicinae sensu stricto, and the asymmetrical endosomal sclerites appearing before the other asymmetric traits.